Polimorfismos genético e proteico da enzima conversora de angiotensina na síndrome de pré-eclâmpsia - Krauspenhar, Bruna (2015)
Introduction: Preeclampsia is a disease characterized as high maternal and fetal morbidity and mortality, diagnosed only after 20th gestational week, its etiology is not completely understood and healing is placental removal. It has been looking for biomarkers that allow early diagnosis for a better outcome of the disease. The 90 kDa isoform of Angiotensin Converting Enzyme (ACE), proposed as a new biomarker for hypertension, has not been studied in the preeclampsia syndrome so far. Objective: To evaluate the gene and protein expression, as well as enzymatic activity of ACE in pregnancy induced hypertension. Material and methods: It were included 69 normotensive and preeclampsia syndrome pregnant women at São Lucas Hospital/PUCRS, Porto Alegre/ RS- Brazil. Blood sample was collected to perform ACE genetic polymorphism, and three urine samples (during pregnancy, after delivery and at least 3 months after delivery) were taken to perform ACE protein polymorphism and enzymatic activity. This study was conducted through a partnership between Nephrology Service from PUCRS and Kidneys and Hormones from UNIFESP Laboratories research. Results: Scientific paper was published in Medical Hypotheses journal, entitled “Angiotensin Converting Enzyme 90 kDa isoform: Biomarker for diagnosis of preeclampsia?” that described the hypotheses of this research. Comparing the participants clinical data among the groups (Normal pregnant, pure preeclampsia, superimposed preeclampsia), statistical significancy was observed between obstetric gestational age, blood pressure, newborn weight (p< 0.001) and placental weight (p= 0.030). Hypertension familial history compared with ACE genotypes (p= 0.017) suggests allele I involvement. Enzymatic activity ZPhe and Hhl ratio was different during the gestational period (p< 0.025), and also in relation to the ACE genotypes (p< 0.001). ZPhe and HhL isolated enzymatic activity also, in relation to the ACE genotypes, was not statistically different (p = 0.83 e p = 0.16, respectively). The protein polymorphism was not performed due to some technique problems, but this activity will be finished as soon as possible. Conclusion: It seems that allele I is associated with the hypertension familial history, and the genotypes that have this allele (ID, II) are predominantly present in pregnant women with preeclampsia. Enzymatic activity of Zphe/Hhl shows different behavior during the gestational period, and it also change according to genotypes classification. The data suggest that the mechanism involved in essential hypertension can be different from those involved in transient and spontaneous hypertension triggered pregnancy induced hypertension.